A 3-Year Adaptation Study of Three Distinct Grapevine Cultivars under Midwestern Field Conditions. Issue 1 (2nd January 2017) - Ennahli, Said; Kadir, Sorkel; Khatamian, Houchang; Scurlock, David; Hanine, Hafida
ABSTRACT: Simultaneous responses of American (Concord), European (Pinot Noir), and American-European hybrid (Traminette) cultivars to seasonal and diurnal variation in field environmental conditions were assessed to propose suitable cultivars for potential use for selection and breeding in grapevines in dry areas. 'Pinot Noir' had higher gas exchange parameters, higher water potential, and chlorophyll fluorescence, while 'Concord' had the lowest values in all three seasons and experienced moderate stress by the end of each season. The dry conditions in 2005 caused water potential to decline sharply compared to values recorded in 2004 and 2006. 'Pinot Noir' and 'Traminette' exhibited a mild stress, while 'Concord' exhibited a moderate stress in 2006. Photosynthetic rate decreased slightly during the summer with a slight recovery at the beginning of September, and did not differ across the seasons among cultivars. Stomatal conductance followed the same pattern. However, in both 2004 and 2005, stomatal conductance dropped sharply late in the season because of frequently occurring high temperatures that were greater than 32 °C. Maximum morning values of Fv/Fm were within the optimal range. The study suggests the presence of marginal photoinhibition during mid-summer in Concord cultivars, because no full recovery of photochemical efficiency early in the evening was observed. The European cultivar (Pinot Noir) and the American-European hybrid (Traminette) are more adapted to field conditions in Kansas than Concord cultivars. However, high cold-mortality of Pinot Noir due to high sensitivity to cold winter temperature makes the hybrid cultivars the most suitable cultivar for Midwest regions with relatively cold winters.